A Dual‐Ligand Strategy to Regulate the Nucleation and Growth of Lead Chromate Photoanodes for Photoelectrochemical Water Splitting. Issue 29 (8th June 2022) - Zhou, Hongpeng; Zhang, Deyun; Gong, Xiangnan; Feng, Zhendong; Shi, Ming; Liu, Yang; Zhang, Chengbo; Luan, Peng; Zhang, Pengfei; Fan, Fengtao; Li, Rengui; Li, Can
Abstract: Photoelectrochemical (PEC) water splitting for renewable hydrogen production has been regarded as a promising solution to utilize solar energy. However, most photoelectrodes still suffer from poor film quality and poor charge separation properties, mainly owing to the possible formation of detrimental defects including microcracks and grain boundaries. Herein, a molecular coordination engineering strategy is developed by employing acetylacetone (Acac) and poly(ethylene glycol) (PEG) dual ligands to regulate the nucleation and crystal growth of the lead chromate (PbCrO4 ) photoanode, resulting in the formation of a high‐quality film with large grain size, well‐stitched grain boundaries, and reduced oxygen vacancies defects. With these efforts, the nonradiative charge recombination is efficiently suppressed, leading to the enhancement of its charge separation efficiency from 47% to 90%. After decorating with Co–Pi cocatalyst, the PbCrO4 photoanode achieves a photocurrent density of 3.15 mA cm −2 at 1.23 V (vs RHE under simulated AM1.5G) and an applied bias photon‐to‐current efficiency (ABPE) of 0.82%. This work provides a new strategy to modulate the nucleation and growth of high‐quality photoelectrodes for efficient PEC water splitting. Abstract : A dual‐ligand growth strategy in fabricating high‐quality PbCrO4 thin film is demonstrated by slowing down crystal growth and inducing faster heterogeneous nucleation during annealing process. The dual‐ligand strategy can effectively improve crystallinity, reduce defect density, and subsequently boosts superior charge separation efficiency up to ≈90%.